A NOVEL 5 TITIK 1 KOMA BY MUHAMMAD KAMAL IHSAN ON PERSPECTIVE AL-GHAZALI’S SUFISM - Khairatun Nisa (Jurnal Ilmiah Ilmu Ushuluddin, 2020)
Based on the results of the study, it can be concluded that the novel 5 Titik 1 Koma by Muhammad Kamal Ihsan contains aspects of akhlaki and amali sufism that are in line with Sufism Al-Ghazali's thinking, especially in the stages (maqâmat) and conditions (ahwâl) by which a person sâlik. However, there are differences in the formulation of elements of happiness that must be possessed, even though basically they are interconnected in their implementation.This novel tells the story of the struggle of a mute woman who is studying in Egypt named Zaritsa through the main character named Ihsan. Zaritsa 's determination has provided extraordinary experiences for other characters in this novel, so that they become better people and are more grateful to God for all the pleasures they feel. In addition to containing stories, this novel also contains an explanation of five points and one comma itself, namely gratitude, patience, confidence, sincerity, honesty, and love.The Sufism aspect contained in this novel which is also explained by Al-Ghazali in the form of maqamat is a spiritual level that must be attained by a sâlik and ahwal, namely the mental condition of a salik. Maqâmât and ahwâl contained include: Repentance, patience and gratitude, zuhud, tawakkal, mahabbah (love), sincerity, and honesty. Everything is in accordance with what was mentioned by Al-Ghazali, but there are differences in the use of terms such as the use of sincerity in the face of all the tests that Al-Ghazali called ridha.In addition to Maqamat and Ahwal, this novel also contains the formulation of happiness that will be achieved by Jiaka humans to have gratitude, patience, confidence, sincerity, honesty, and love. The formulation of happiness is in line with Al-Ghazali's view, but Al-Ghazali uses a different language, namely knowing oneself, knowing God, knowing the world, and knowing the hereafter. By recognizing these four things, then someone will surely be grateful, patient, confident, sincere, honest, and love as mentioned by the novelist.The suggestions conveyed based on this research are novel writers, especially Islamic novels to better popularize Sufism values, given the large number of people interested in reading novels compared to reading religious books directly. Researchers are expected to enrich their studies with other methods of literary research, so as to add to the treasures for research in literature, in the form of novels, films, poems, short videos, poems, songs and so on.